An essay on the political functions of corruption - Scott, James C. (1967)
Corruption of public officials poses a special problem in developing nations because of the governor's dominant role in the economy and because the legal systems are not based on indigenous social traditions. When special interest groups or minorities have no legal channels of influence, corruption may be an effective method of influencing government policy. Corruption also represents a governments efforts to cope informally with a rate of social change that is beyond the capabilities of the formal political system.In the West and underdeveloped countries corruption has given new groups the opportunity to influence the government without resorting to to violence. In areas where loyalties are restricted to kinsmen and parochial groups, corruption may be the only way to foster commitment to a wider group, such as political party. In parochial corruption, beneficiaries are those having special connections, while wealthy elites will compete for favors in market corruption. The beneficiaries of corruption also depend on power relationships among the rules, the bureaucracy, the political parties if they exist. The ruling elite will always profit to some extent, but in a system with competitive parties, benefits extend to party cader and voters, as evidenced in pork barrel legislation and legalized patronage. Market corruption can promote economic development as seen in the Philippines, Thailand, and Malaysia, unless it raises business costs beyond the profitable level or unless uncertainty about governmental decisions prevails. Corruption practices which restrict or distort market forces can hinder economic growth. Corruption which contributes to development by rewarding wealthy elites can impede political integration since it excludes voters and parochial groups. Market corruption can also affect the pricing system and harm community interests when there are no centralized controls.
Photocopy.
Reprinted from.
Includes bibliographical references.
Keywords: Political corruption -- Essays; Corruption -- Study and teaching; Essays